A modified high-nickel positive electrode material and a preparation method thereof
Patent Information
- Application Number
- CN202611300372.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-27
AI Technical Summary
然而,在追求超高能量密度的过程中,材料的应用瓶颈日益凸显,表现出以下问题:第一、结构稳定性不足:Ni含量的增加直接提高了氧化还原电位,导致材料在高脱锂态下晶格结构不稳定,易发生不可逆的相变,严重影响循环寿命
[0022]非晶Li3PO4填充在高镍三元正极材料表面包覆多孔金属氧化层的孔道内,形成三维连续离子通道,Li⁺可以快速通过这些通道到达颗粒表面,同时由于P-O键能高,非晶Li3PO4表现出优异的化学稳定性,配合金属氧化层在正极材料与电解液之间形成物理屏障,避免表面副反应,并同时提升了高镍三元正极材料稳定性和倍率性能,可以进一步推动高镍三元正极材料在高功率电池中的产业化应用。
Smart Images

Figure CN122991971A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery material technology, specifically relating to a modified high-nickel cathode material and its preparation method. Background Technology
[0002] In recent years, with the rapid development of cutting-edge equipment industries such as electric vehicles, drones, and robots, the market has placed unprecedented demands on the energy density, output power, and cycle life of lithium-ion batteries. As the core of battery technology, breakthroughs in the performance of cathode materials are key to solving the "range anxiety" and "power bottleneck" issues. Against this backdrop, high-energy-density ternary cathode materials (LiNi) have become increasingly important. x Co y Mn 1-x-y O2, or LiNi x Co y Al 1-x-y O2 has become a current research hotspot. Among them, the high-nickel ternary system (Ni content x≥0.8) is widely recognized as one of the most promising cathode materials for achieving high energy density batteries due to its extremely high theoretical specific capacity, which can reach up to 200mAh / g in practical applications. However, in the pursuit of ultra-high energy density, the application bottleneck of the material is becoming increasingly prominent, exhibiting the following problems: First, insufficient structural stability: The increase in Ni content directly increases the redox potential, leading to instability of the lattice structure of the material in the high delithiation state, which easily causes irreversible phase transitions and seriously affects cycle life. Second, hindered interfacial kinetics: Ternary materials are prone to lattice oxygen loss and cation mixing (Ni²) in the high delithiation state. + (migrating to the Li layer), resulting in Li + Clogged transmission channels reduce rate performance. Third: Severe interfacial side reactions and highly active Ni surface. 3 + / Ni 4+ When in contact with the electrolyte, severe side reactions occur, forming a CEI film that increases impedance and triggers the dissolution of transition metals, exacerbating battery polarization and causing irreversible capacity loss, thus limiting the practical application of high-nickel materials at high rates.
[0003] In existing technologies, surface coating modification is one of the important research directions for ternary materials. Metal oxides such as Al2O3, ZrO2, MgO, and ZnO are used for coating modification. These inert or low-activity oxide layers have excellent surface structural stability and can isolate the cathode and electrolyte to a certain extent, suppress interfacial side reactions, and alleviate structural stress. However, those skilled in the art generally face a difficult technical trade-off. Since traditional metal oxide coatings are ion insulators, Li⁺ can only slowly penetrate through defects or grain boundaries. This is the fundamental reason for the high impedance at high rates. While providing a stable interface as a coating layer, it inevitably increases the interfacial charge transfer impedance, becoming a barrier to the rapid transport of lithium ions and electrons. This severely limits the performance of the material under high-rate charge and discharge conditions, making it impossible to simultaneously achieve structural stability and high-rate kinetics. Summary of the Invention
[0004] To address the technical shortcomings of existing high-nickel ternary cathode materials, this invention provides a method for preparing a modified high-nickel cathode material, comprising the following steps:
[0005] S1: Place the high-nickel cathode material in a vacuum drying oven and dry it at 100-120℃ for 6-12 hours for later use;
[0006] S2: The dried high-nickel cathode material is added to a mixed solvent of anhydrous ethanol and deionized water and ultrasonically dispersed and stirred to form a suspension;
[0007] S3: Add template agent to the suspension formed in step S2 and stir until completely dissolved to obtain a mixture;
[0008] S4: Add the metal oxide precursor to the mixture in step S3 and control the pH of the system to 6-7. After stirring for 2-4 hours, centrifuge to obtain solid particles.
[0009] S5: Extract the solid particles from step S4 with anhydrous ethanol and then vacuum dry them in a drying oven to obtain solid powder.
[0010] S6: Place the solid powder obtained in step S5 into the high-purity nitrogen replacement chamber of the atomic layer deposition reactor, purge the reaction chamber with high-purity nitrogen to remove residual air in the chamber, and after replacement, raise the temperature to 220°C at 5°C / min and hold for 30min.
[0011] S7: Introduce vaporized lithium and phosphorus sources, alternately pulse and simultaneously intermittently introduce nitrogen and oxygen to purge, and cyclically deposit multiple times to form high-nickel cathode particles coated with a porous metal oxide layer. Amorphous Li3PO4 is generated in situ on the pore walls of the porous material.
[0012] Furthermore, the chemical formula of the high-nickel cathode material in step S1 is LiNi. x Co y Mn z O2 (0.8≤x<1, x+y+z=1).
[0013] Furthermore, the metal oxide precursor is any one of aluminum alkoxide, zirconium alkoxide, tetrabutyl titanate, magnesium acetate, and zinc acetate.
[0014] Furthermore, the template agent is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer or hexadecyltrimethylammonium bromide.
[0015] Furthermore, the lithium source is any one of lithium tert-butoxide and lithium hexamethyldisilamide; the phosphorus source is any one of trimethyl phosphate and triethyl phosphate.
[0016] Furthermore, the temperature after heating in step S6 is 200℃~300℃.
[0017] Further, the sequence of a deposition pulse cycle in step S7 is as follows: first, a lithium source pulse cycle for 0.5~2s, followed by nitrogen purging for 15~30s; then a phosphorus source pulse for 1~3s; followed by nitrogen purging for 15~30s; then an oxygen source pulse for 0.5~1.5s, and finally nitrogen purging for 15~30s.
[0018] Furthermore, the number of deposition pulse cycles in step S7 is 50 to 100.
[0019] Another aspect of the present invention provides a high-nickel cathode material prepared by the above preparation method, comprising a porous metal oxide layer, wherein the thickness of the porous metal oxide layer is 5-20 nm, the pore size of the porous metal oxide layer is 2-10 nm, and lithium phosphate is deposited on the pore walls of the porous metal oxide layer.
[0020] Furthermore, the total weight of metal elements in the porous metal oxide layer accounts for 0.5% to 2% of the total weight of the cathode material.
[0021] This invention employs a sol-gel method combined with a template agent to construct a continuous and uniform mesoporous metal oxide coating layer on the surface of high-nickel ternary particles. Then, an ultrathin amorphous Li3PO4 is grown on the inner wall of the nanopores using atomic layer deposition (ALD) technology, forming a composite interface structure with metal oxide as the framework and Li3PO4 as the fast ion conductor of the pore wall. This structure can both physically isolate the electrolyte to suppress side reactions and provide a low-impedance lithium-ion transport path.
[0022] Amorphous Li3PO4 fills the pores of the porous metal oxide layer on the surface of high-nickel ternary cathode material, forming a three-dimensional continuous ion channel. Li⁺ can quickly reach the particle surface through these channels. At the same time, due to the high bond energy of PO, amorphous Li3PO4 exhibits excellent chemical stability. Together with the metal oxide layer, it forms a physical barrier between the cathode material and the electrolyte, avoiding surface side reactions and improving the stability and rate performance of the high-nickel ternary cathode material. This can further promote the industrial application of high-nickel ternary cathode materials in high-power batteries. Attached Figure Description
[0023] Figure 1 The results show the cycle test results of batteries prepared using the cathode materials of Example 1 and Comparative Example 1 of this invention. Detailed Implementation
[0024] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
[0025] Example 1
[0026] S1: Add 100g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) cathode material was vacuum dried at 120℃ for 12 hours before use.
[0027] S2: Add 200 mL of anhydrous ethanol and 10 mL of deionized water to the reaction vessel and stir to prepare a mixed solvent. Add the dried NCM811 from step S1 to the above mixed solvent and ultrasonically disperse for 2 min. Keep stirring throughout the process to maintain the system in uniform suspension and prepare a suspension.
[0028] S3: Add 2.0g of template agent P123 (chemical name: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, EO) to the suspension in step S2. 20 PO 70 EO 20 Stir until completely dissolved;
[0029] S4: Dissolve 6.0 g of aluminum isopropoxide in 50 mL of anhydrous ethanol and slowly add it dropwise to the suspension in step S3. During the dropwise addition, adjust the pH of the system to 6.0-7.0 using 0.5 mol / L dilute ammonia. After the dropwise addition is complete, stir the reaction in a 25°C water bath for 4 h. After the reaction is complete, centrifuge to obtain solid powder.
[0030] S5: The solid powder obtained in step S4 was extracted by soaking in anhydrous ethanol three times, each time for 1 hour, with low-speed stirring to remove the P123 template agent. Then it was vacuum dried at 60°C for 6 hours to obtain the porous Al2O3-coated NCM811 material.
[0031] S6: The above-mentioned porous Al2O3-coated NCM811 powder is loaded into a 250mL powder atomic layer deposition reactor, high-purity nitrogen is introduced to replace the chamber for 30min, the temperature is raised to 220℃ and held for 30min.
[0032] Step S7: Using lithium tert-butoxide as the lithium source, the lithium source bottle is heated to 180°C to vaporize it, with a pulse time of 1.5s; using trimethyl phosphate as the phosphorus source, the phosphorus source bottle is heated to 80°C to vaporize it, with a pulse time of 2s; high-purity nitrogen is used as the purging gas, with a purging time of 20s / cycle; high-purity oxygen is used as the oxidizing oxygen source with a pulse of 0.5s. The process is repeated 80 times in the order of lithium source pulse - nitrogen purging - phosphorus source pulse - nitrogen purging - oxygen source pulse - nitrogen purging to generate amorphous Li3PO4 in situ on the mesoporous pore walls.
[0033] S8: After deposition, the material is vacuum dried at 120℃ for 4 hours under a nitrogen atmosphere and then cooled to room temperature to obtain the composite modified NCM811@m-Al2O3 / LPO cathode material.
[0034] Comparative Example 1
[0035] Comparative Example 1: Li3PO4 was coated with Al2O3 but not deposited using ALD. 4, The specific steps are as follows:
[0036] S1: Add 100g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) cathode material was vacuum dried at 120℃ for 12 hours before use.
[0037] S2: Add 200 mL of anhydrous ethanol and 10 mL of deionized water to the reaction vessel and stir to prepare a mixed solvent. Add the dried NCM811 from step S1 to the above mixed solvent, and ultrasonically disperse for 2 min. Keep stirring throughout the process to maintain the uniform suspension of the system and prepare a suspension.
[0038] S3: Add 2.0g of template agent P123 to the suspension and stir until completely dissolved;
[0039] S4: Dissolve 6.0 g of aluminum isopropoxide in 50 mL of anhydrous ethanol and slowly add it dropwise to the suspension. During the dropwise addition, adjust the pH of the system to 6.0-7.0 with 0.5 mol / L dilute ammonia. After the dropwise addition is complete, stir the reaction in a 25°C water bath for 4 h. After the reaction is complete, centrifuge to obtain solid powder.
[0040] S5: The obtained solid powder was extracted by soaking in anhydrous ethanol three times, each time for 1 hour, with low-speed stirring to remove the P123 template agent. Then it was vacuum dried at 60°C for 6 hours to obtain porous Al2O3-coated NCM811@m-Al2O3 material.
[0041] Example 2
[0042] S1: Add 100g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) cathode material was vacuum dried at 120℃ for 12 hours before use.
[0043] S2: Add 200 mL of anhydrous ethanol and 10 mL of deionized water to the reaction vessel and stir to prepare a mixed solvent. Add the dried NCM811 from step S1 to the above mixed solvent, and ultrasonically disperse for 2 min. Keep stirring throughout the process to maintain the uniform suspension of the system and prepare a suspension.
[0044] S3: Add 2.0g of template agent P123 to the suspension and stir until completely dissolved;
[0045] S4: Dissolve 4.0 g of zirconium n-propoxide in 50 mL of anhydrous ethanol and slowly add it dropwise to the suspension. During the dropwise addition, adjust the pH of the system to 6.5–7.5 using 0.5 mol / L dilute nitric acid. After the dropwise addition is complete, stir the reaction in a 25°C water bath for 4 h. After the reaction is complete, centrifuge to separate the contents.
[0046] S5: The obtained solid was extracted by soaking in anhydrous ethanol three times, each time for 1 hour, with low-speed stirring to remove template agent P123. Then it was vacuum dried at 60°C for 6 hours to obtain porous ZrO2-coated NCM811 material.
[0047] S6: The porous ZrO2-coated NCM811 material obtained in step S5 is loaded into a 250mL powder atomic layer deposition reactor, high-purity nitrogen is introduced to replace the chamber for 30min, the temperature is raised to 220℃ and held for 30min.
[0048] S7: Using lithium tert-butoxide as the lithium source, it is heated to 180℃ and vaporized, with a pulse of 1.5s; using trimethyl phosphate as the phosphorus source, it is heated to 80℃ and vaporized, with a pulse of 2s, and purged with high-purity nitrogen for 20s / cycle, using high-purity nitrogen as the purging gas, with a purging time of 20s / cycle; using high-purity oxygen as the oxidizing oxygen source with a pulse of 0.5s, the process is repeated 80 times in the order of lithium source pulse - nitrogen purging - phosphorus source pulse - chlorine purging - oxygen source pulse - nitrogen purging, to generate amorphous Li3PO4 in situ on the mesoporous pore walls;
[0049] S8: After deposition, the material is vacuum dried at 120°C for 4 hours under a nitrogen atmosphere and then cooled to room temperature to obtain the composite modified NCM811@m-ZrO2 / LPO cathode material.
[0050] Comparative Example 2
[0051] S1: Add 100g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) cathode material was vacuum dried at 120℃ for 12 hours before use.
[0052] S2: Add 200 mL of anhydrous ethanol and 10 mL of deionized water to the reaction vessel, add the dried NCM811 to the above mixed solvent, ultrasonically disperse for 2 min, keep stirring, and maintain the system in uniform suspension to prepare a suspension.
[0053] S3: Add 2.0g of P123 template agent to the suspension prepared in S2 and stir until completely dissolved;
[0054] S4: Dissolve 4.0 g of zirconium propoxide (Zr(OPr)4) in 50 mL of anhydrous ethanol and slowly add it dropwise to the suspension. During the dropwise addition, adjust the pH of the system to 6.5-7.5 with dilute nitric acid. After the dropwise addition is complete, stir the reaction in a water bath at 25 °C for 4 h. After the reaction is complete, centrifuge the mixture and wash the precipitate three times with anhydrous ethanol.
[0055] S5: The obtained solid was extracted three times by soaking in anhydrous ethanol, each time for 1 hour, with low-speed stirring to remove the P123 template agent. Then it was vacuum dried at 60°C for 6 hours to obtain porous ZrO2-coated NCM811@m-ZrO2 material.
[0056] Example 3
[0057] S1:100gLiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) cathode material was vacuum dried at 120℃ for 12 hours before use.
[0058] S2: Add 200 mL of anhydrous ethanol and 10 mL of deionized water to the reaction vessel, add the dried NCM811 to the above mixed solvent, and sonicate for 2 min. Keep stirring throughout the process to maintain the uniform suspension of the system.
[0059] S3: Add 2.0g of P123 template agent to the suspension and stir until completely dissolved;
[0060] S4: Dissolve 5.3g magnesium isopropoxide in 50mL of anhydrous ethanol and slowly add it dropwise to the suspension. During the dropwise addition, adjust the pH of the system to 6.0-7.0 with 0.5mol / L dilute ammonia. After the dropwise addition is complete, stir the reaction in a 25℃ water bath for 4h. After the reaction is complete, centrifuge and wash the precipitate three times with anhydrous ethanol to obtain solid powder.
[0061] S5: The solid powder obtained in step S3 was extracted by soaking in anhydrous ethanol three times, each time for 1 hour, with low-speed stirring to remove template agent P123. Then it was vacuum dried at 60°C for 6 hours to obtain porous MgO-coated NCM811 material.
[0062] S6: The above porous MgO-coated NCM811 material was loaded into a 250mL powder atomic layer deposition reactor, and high-purity nitrogen was introduced to replace the chamber for 30min. The temperature was raised to 220℃ and held for 30min.
[0063] S7: Using lithium tert-butoxide as the lithium source, it is heated to 180℃ and vaporized, with a pulse of 1.5s; using trimethyl phosphate as the phosphorus source, it is heated to 80℃ and vaporized, with a pulse of 2s, and purged with high-purity nitrogen for 20s / cycle, using high-purity nitrogen as the purging gas, with a purging time of 20s / cycle; using high-purity oxygen as the oxidizing oxygen source with a pulse of 0.5s, the process is repeated 80 times in the order of lithium source pulse - nitrogen purging - phosphorus source pulse - chlorine purging - oxygen source pulse - nitrogen purging, to generate amorphous Li3PO4 in situ on the mesoporous pore walls;
[0064] S8: After deposition, the material is vacuum dried at 120°C for 4 hours under a nitrogen atmosphere and then cooled to room temperature to obtain the composite modified NCM811@m-MgO / LPO cathode material.
[0065] Comparative Example 3
[0066] S1: Add 100g LiNi 0.8 Co 0.1 Mn 0.1 The O2 (NCM811) cathode material was vacuum dried at 120℃ for 12 hours before use.
[0067] S2: Add 200 mL of anhydrous ethanol and 10 mL of deionized water to the reaction vessel, add the dried NCM811 to the above mixed solvent, and sonicate for 2 min. Keep stirring throughout the process to maintain the uniform suspension of the system.
[0068] S3: Add 2.0g of P123 template agent to the suspension and stir until completely dissolved;
[0069] S4: Dissolve 5.3g magnesium isopropoxide in 50mL of anhydrous ethanol and slowly add it dropwise to the suspension. During the dropwise addition, adjust the pH of the system to 6.0-7.0 with 0.5mol / L dilute ammonia. After the dropwise addition is complete, stir the reaction in a 25℃ water bath for 4h. After the reaction is complete, centrifuge and wash the precipitate three times with anhydrous ethanol to obtain solid powder.
[0070] S5: The solid powder obtained in step S4 was extracted by soaking in anhydrous ethanol three times, each time for 1 hour and with low-speed stirring to remove template agent P123. Then it was vacuum dried at 60°C for 6 hours to obtain porous MgO-coated NCM811@m-MgO material.
[0071] Electrochemical performance testing
[0072] Using the high-nickel cathode materials prepared in the various embodiments and comparative examples of this invention, a 2.0 Ah small pouch cell was fabricated, and its electrochemical performance was tested. The specific steps are as follows:
[0073] The positive electrode active materials obtained in each embodiment and comparative example were stirred evenly with the same binder, conductive agent, and N-methylpyrrolidone under dew point conditions to obtain positive electrode slurries, which were then coated and rolled to obtain positive electrode sheets. The same negative electrode active material, binder, conductive agent, and deionized water were stirred evenly to obtain negative electrode slurries, which were then coated and rolled to obtain negative electrode sheets.
[0074] The positive and negative electrode sheets prepared above were used to prepare a 2.0Ah soft-pack battery cell through a battery cell manufacturing process. Then, electrochemical performance tests were performed at room temperature: the charge-discharge range was 3.0-4.25V, and the cell capacity was calibrated by 0.33C charge-discharge. Subsequently, the rate discharge performance was tested at 1C, 2C, 3C, and 4C discharge rates, starting at a 1C charging rate. Then, under the same conditions, after calibration at 0.33C, a 1C cycle test was directly performed to evaluate the electrochemical performance of the material. The electrochemical test used in this application adopted the Blue Electricity test system. Figure 1 The results of the cyclic testing for Example 1 and Comparative Example 1 are shown, with the horizontal axis representing the number of cycles and the vertical axis representing the capacity retention rate.
[0075] Depend on Figure 1 It can be seen that the high-nickel cathode material NCM811 can significantly improve the cycle retention rate of the battery by coating it with oxide. Furthermore, the cycle retention rate can be further improved by atomically depositing lithium phosphate after coating it with oxide.
[0076] Table 1 shows the discharge performance and formation gas generation data of batteries composed of untreated NCM811, various examples and comparative examples of cathode materials.
[0077] Group NCM811 NCM811@m-Al2O3 NCM811@m-Al2O3 / LPO NCM811@m-ZrO2 NCM811@m-ZrO2 / LPO NCM811@m-MgO NCM811@m-MgO / LPO 2C discharge ratio 92.00% 89.30% 95.70% 90.80% 96.20% 88.40% 94.60% Gas production (ml / Ah) 1.30 0.82 0.8 0.83 0.81 0.83 0.8
[0078] The results above show that, compared to simply coating the outer surface of high-nickel ternary NCM811 particles with metal oxide, adding metal oxide and deposited lithium phosphate on the outer surface of high-nickel ternary particles can significantly improve the discharge ratio of the battery by approximately 6 percentage points, and can also improve the formation gas generation.
[0079] The high-nickel cathode material preparation method of this invention involves growing an ultrathin amorphous Li3PO4 on the inner wall of nanopores using atomic layer deposition (ALD) technology on a porous coating layer of metal oxides such as Al2O3, serving as a solid electrolyte interface layer. This solid electrolyte interface layer effectively isolates the cathode from the liquid electrolyte through the metal oxide framework, suppressing interfacial side reactions and improving cycle life. Furthermore, the amorphous Li3PO4 provides low-activation-energy lithium-ion jumping sites (based on the Grotthuss mechanism), constructing a low-impedance, high-kinetic ion transport channel.
[0080] The preparation method of this invention uses amorphous Li3PO4 and is prepared by a low-temperature ALD process, eliminating the need for high-temperature sintering and achieving zero damage to the high-nickel substrate. The high-nickel ternary cathode material prepared by this method is coated with a porous metal oxide layer. Amorphous Li3PO4 is filled into the pores using ALD atomic layer deposition technology, forming three-dimensional continuous ion channels. Li⁺ can quickly reach the particle surface through these channels. Simultaneously, due to the high bond energy of PO, amorphous Li3PO4 exhibits excellent chemical stability. Together with the metal oxide layer, it forms a physical barrier between the cathode material and the electrolyte, preventing surface side reactions.
[0081] The high-nickel ternary cathode material prepared by the method of this invention fundamentally breaks through the technical bottleneck that "stability and rate performance cannot be achieved simultaneously" in high-nickel ternary cathode materials.
[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a modified high-nickel cathode material, characterized in that, Includes the following steps: S1: Place the high-nickel cathode material in a vacuum drying oven and dry it at 100-120℃ for 6-12 hours for later use; S2: The dried high-nickel cathode material is added to a mixed solvent of anhydrous ethanol and deionized water and ultrasonically dispersed and stirred to form a suspension; S3: Add template agent to the suspension formed in step S2 and stir until completely dissolved to obtain a mixture; S4: Add the metal oxide precursor to the mixture in step S3 and control the pH of the system to 6-7. After stirring for 2-4 hours, centrifuge to obtain solid particles. S5: Extract the solid particles from step S4 with anhydrous ethanol and then vacuum dry them in a drying oven to obtain solid powder. S6: Place the solid powder obtained in step S5 into the high-purity nitrogen replacement chamber of the atomic layer deposition reactor, purge the reaction chamber with high-purity nitrogen to remove residual air in the chamber, and after replacement, raise the temperature to 220°C at 5°C / min and keep it at that temperature for 30min. S7: Introduce vaporized lithium and phosphorus sources, alternately pulse and simultaneously intermittently introduce nitrogen and oxygen to purge, and cyclically deposit multiple times to form high-nickel cathode particles coated with a porous metal oxide layer. Amorphous Li3PO4 is generated in situ on the pore walls of the porous material.
2. The method for preparing the modified high-nickel cathode material as described in claim 1, characterized in that, The high-nickel cathode material in step S1 has the chemical formula LiNi. x Co y Mn z O2 (0.8≤x<1, x+y+z=1).
3. The method for preparing the modified high-nickel cathode material as described in claim 2, characterized in that, The metal oxide precursor is any one of aluminum alkoxide, zirconium alkoxide, tetrabutyl titanate, magnesium acetate, and zinc acetate.
4. The method for preparing the modified high-nickel cathode material as described in claim 1, characterized in that, The template agent is one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer or hexadecyltrimethylammonium bromide.
5. The method for preparing the modified high-nickel cathode material as described in claim 1, characterized in that, The lithium source is any one of lithium tert-butoxide and lithium hexamethyldisilamide; the phosphorus source is any one of trimethyl phosphate and triethyl phosphate.
6. The method for preparing the modified high-nickel cathode material as described in claim 1, characterized in that, The temperature after heating in step S6 is 200℃~300℃.
7. The method for preparing the modified high-nickel cathode material as described in claim 6, characterized in that, The sequence of a deposition pulse cycle in step S7 is as follows: first, a lithium source pulse cycle for 0.5~2s, followed by nitrogen purging for 15~30s; then a phosphorus source pulse for 1~3s; followed by nitrogen purging for 15~30s; then an oxygen source pulse for 0.5~1.5s, and finally nitrogen purging for 15~30s.
8. The method for preparing the modified high-nickel cathode material as described in claim 7, characterized in that, The number of deposition pulse cycles in step S7 is 50 to 100.
9. A modified high-nickel cathode material prepared by the preparation method according to claims 1-8, characterized in that the high-nickel cathode material includes a porous metal oxide layer, the thickness of the porous metal oxide layer is 5-20 nm, the pore size of the porous metal oxide layer is 2-10 nm, and lithium phosphate is deposited on the pore walls of the porous metal oxide layer.
10. The modified high-nickel cathode material as described in claim 9, characterized in that, The total weight of metal elements in the porous metal oxide layer accounts for 0.5% to 2% of the total weight of the cathode material.